2019
DOI: 10.1111/jth.14594
|View full text |Cite
|
Sign up to set email alerts
|

The roles of factor Va and protein S in formation of the activated protein C/protein S/factor Va inactivation complex

Abstract: BackgroundActivated protein C (APC)‐mediated inactivation of factor (F)Va is greatly enhanced by protein S. For inactivation to occur, a trimolecular complex among FVa, APC, and protein S must form on the phospholipid membrane. However, direct demonstration of complex formation has proven elusive.ObjectivesTo elucidate the nature of the phospholipid‐dependent interactions among APC, protein S, and FVa.MethodsWe evaluated binding of active site blocked APC to phospholipid‐coated magnetic beads in the presence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 52 publications
3
28
0
1
Order By: Relevance
“…16,52,53,99 Protein S Gla36 and Asp95 (dark green) are both needed for APC cofactor function and we recently hypothesized that they may be part of a FVa interaction site. 46,50,51 This is in agreement with a previously published study, identifying Gla-TSR residues 37-50 (light green) being involved in FVa binding. 56 The epidermal growth factor 2 (EGF2) domain has also been shown to be essential for the APC cofactor function of protein S, suggesting its involvement in important protein-protein interactions.…”
Section: F I G U R Esupporting
confidence: 93%
See 4 more Smart Citations
“…16,52,53,99 Protein S Gla36 and Asp95 (dark green) are both needed for APC cofactor function and we recently hypothesized that they may be part of a FVa interaction site. 46,50,51 This is in agreement with a previously published study, identifying Gla-TSR residues 37-50 (light green) being involved in FVa binding. 56 The epidermal growth factor 2 (EGF2) domain has also been shown to be essential for the APC cofactor function of protein S, suggesting its involvement in important protein-protein interactions.…”
Section: F I G U R Esupporting
confidence: 93%
“…Specifically, Arg306 cleavage was severely reduced. In a recent follow-up study, 46 we showed that this was in part due to reduced affinity toward negatively charged phospholipid membranes.…”
Section: F I G U R Ementioning
confidence: 85%
See 3 more Smart Citations